Activities for Rehabilitation and Development of Disabled Person - Yaemsuksawat, Yuphadee; Wiyaboon, Saowanee (Rajapark Journal, 2023)
The director of the Sirarom Disabled Person Service Center in Rayong Province set the project as "Four Activities for Therapy, Rehabilitation, and Development of Disabled Persons," following the Empowerment of Persons with Disabilities Act, B.E. 2560–2564. These objectives of the project were: 1) to rehabilitate the disabled person both physically and mentally by using 4 forms of alternative therapy activities; 2) to develop the potential of social skills and interpersonal interactions for people with disabilities; 3) to provide the knowledge for caregivers to apply systematically and appropriately in helping people with disabilities; and 4) to enable people with disabilities and their caregivers to know about how to solve problems and live happily together. There were four activities for therapy: 1) hippotherapy; 2) hydrotherapy or aqua therapy; 3) music therapy; and 4) art therapy. The targets of the project were disabled people (46 people) and caregivers (46 people), for a total of 92 people. The past operations had been in accordance with all four objectives. Working with disabled people and their families was highly sensitive. All activities must be organized by the specialists who have the knowledge to create positive interactions, provide close convenience, give the right advice, and follow up on the self-development of the disabled person. There was a movement of the body in response to the music. The emotional relaxation that affects the development of the body. A disabled person must understand the relationship between the movement and the music to develop both physically and mentally.